Impact of TEACH: A Virtual Pedagogical Model for Teaching English as a Foreign Language. - García, William Ricardo Ortiz; Urbina, Johanna Patricia López (Enunciación, 2026)
This article proposes a virtual pedagogical model for English language teaching that is based on five dimensions: the technological-communicative dimension, the educational-pedagogical dimension, action-based research, competency development, and holistic learning. Its implementation involved 22 students from a bachelor's program in Languages with an emphasis on English at a Colombian university. This study was conducted in three phases: the creation of the TEACH model for virtual learning environments; the adaptation of the syllabus, based on content and language integrated learning (CLIL) and on problem-based learning (PBL) within the framework of an English-taught course; and data collection and analysis through interviews, Likert-scale surveys, observation, and learning analytics. The thematic analysis revealed three categories, yielding results related to interaction and research skills, the impact of task design, problem solving, and learning through experience. The findings highlight the interrelation of these aspects within the TEACH model, demonstrating improvements in English language learning. This study concludes that the model positively impacted learning by anticipating objectives, fostering critical thinking, enhancing communication, and facilitating implicit learning. Additionally, the structured interaction and the design of authentic, content-meaningful tasks played a key role in reinforcing learners' linguistic performance and engagement in real communication.